Administration of Combined Exogenous L-arginine and Ascorbic Acid Attenuates Potassium Bromate-Induced Renal and Hepatic Toxicity (Nigerian Journal of Pharmaceutical Research, 2024)
Background: The use of potassium bromate (KBrO3) as food additive is still widespread and there is need to search for agents with protective effect against KBrO3-induced toxicity.Objective: In this study, the protective effects of L-arginine, ascorbic acid, and their combined regimen on KBrO3-induced renal and hepatic toxicity were investigated in Wistar rats.Methods: Five groups of male rats were used for the study. Group A was given distilled water (control), and group B was treated with KBrO3 only. In addition to KBrO3, groups C, D, and E were given L-arginine, ascorbic acid, and combined L-arginine and ascorbic acid respectively. After 28-day treatment, blood samples were taken for biochemical analysis; liver and kidney were harvested for histological examination.Results: KBrO3 significantly (p < 0.05) raised serum levels of creatinine, urea, ALT, and AST compared to distilled water-treated control. Levels of SOD, CAT, and GPx were also significantly reduced. No significant changes in these parameters were observed with ascorbic acid and L-arginine given separately. Treatment with combined regimen of L-arginine and ascorbic acid resulted in significant (p < 0.05) reduction in the serum levels of creatinine, AST and ALT, and significant increase in the serum levels of SOD, CAT and GPx compared to the control. The distortions induced by KBrO3 in the structural architecture of renal and hepatic tissues were largely reduced in rats treated with combined ascorbic acid and L-arginine.Conclusion: The study showed that L-arginine and ascorbic acid synergistically attenuate KBrO3-induced renal and hepatic toxicity.
Keywords: Potassium bromate; L-arginine; ascorbic acid; liver; kidney